PANDANGAN MASYARAKAT MELAYU SAMBAS TERHADAP ADAT KEMPONAN DI DESA LUBUK DAGANG KECAMATAN SAMBAS KABUPATEN SAMBAS - NIM. A1012181007, ALIF KHAIRIL (Jurnal Fatwa Hukum, 2024)
Abstrac Lubuk Dagang Village, Sambas District, Sambas Regency, is generally inhabited by the Sambas Malay community. One of the traditional customs that still applies to the Sambas Malay community to this day is the traditional kemponan tradition. Kemponan according to the Malay Sambas is a belief in the existence of a catastrophe (bad event) that can befall a person if he refuses to eat or drink offered without tasting or touching the food. In applying the traditional Kemponan tradition, it is only enough to reach or touch the food or drink that has been served to us. This must be done so that we can avoid the disaster that will befall if we do not carry out the traditional kemponan tradition.The main problems in this study are as follows: To obtain data and information about the kemponan custom in the village of Lubuk Trade, Sambas district, Sambas district, To reveal the types or varieties of Kemponan known in Sambas, To reveal the legal consequences for the Sambas Malay community who do not apply kemponan adat in Lubu Trade Village, Sambas District, Sambas Regency, To express the efforts of traditional leaders or leaders in Lubuk Trade Village, Sambas District, Sambas Regency. This research method uses empirical law with descriptive research properties, namely a study carried out to accurately describe the characteristics of individuals, the circumstances at which the research was carried out, Malay traditional elders in Lubuk Trade village, Sambas district, Sambas district, 26 families of hamlets throughout the sub-district of Lubuk Trade village, Sambas district. samba district.The kemponan traditional tradition is very easy to implement because it is only enough to reach a food or drink that has been served to us, the factor that causes the kemponan traditional tradition is to avoid the calamity that will come to us if we are already kemponan. Legal consequences if you don't apply the traditional kemponan tradition, you will get a catastrophe or an accident that can even take your life. Efforts that can be made to continue to be able to preserve the traditional kemponan tradition is to socialize in detail to the Malay Sambas community because there are still Sambas Malay people who still have a bad view of the Kemponan traditional tradition. So it would be great if the Sambas Malay traditional institution held outreach to the community regarding the traditional Kemponan tradition.Keywords: Adat, Kemponan, Sambas Malay Abstrak Desa Lubuk Dagang Kecamatan Sambas Kabupaten Sambas, pada umumnya di diami oleh masyarakat Melayu Sambas. Salah Satu adat istiadat yang masih berlaku pada masyarakat Melayu Sambas sampai saat ini adalah adat kemponan. kemponan menurut Melayu Sambas yaitu kepercayaan tentang adanya malapetaka (kejadian buruk) yang dapat menimpa seseorang jika menolak makanan atau minuman yang ditawarkan tanpa mencicipi atau menyentuh makanan tersebut. Dalam menerapkan adat Kemponan yaitu hanya cukup dengan menjapai atau menyentuh makanan atau minuman yang telah disuguhkan terhadap dirikita. Hal itu wajib dilakukan agar kita dapat terhindar dari malapetaka yang akan menimpa jika tidak menjalankan adat kemponan.Yang menjadi permasalahan pokok dalam penelitian ini adalah sebagai berikut: Untuk mendapatkan data dan informasi tentang adat kemponan di desa lubuk dagang kecamatan sambas kabupaten sambas, Untuk mengungkapkan macam atau ragam kemponan yang dikenal di sambas, Untuk mengungkapkan akibat hukum bagi masyarakat Melayu Sambas yang tidak menerapkan adat kemponan di desa lubu dagang kecamatan sambas kabupaten sambas, Untuk mengungkapkan upaya pemuka atau ketua adat di desa lubuk dagang kecamatan sambas kabupaten sambas. Metode Penelitian ini menggunakan hukum empiris dengan sifat penelitian deskriptif yaitu suatu penelitian yang dilakukan untuk menggambarkan secara tepat sifat-sifat individu, keadaan saat penelitian yang dilaukan, sesepuh adat melayu desa lubuk dagang kecamatan sambas kabupaten sambas, 26 KK dusun sebenua desa lubuk dagang kecamatan sambas kabupaten sambas.Adat kemponan mudah sekali dalam menerapkannya karena hanya cukup dengan menjapai suatu makanan atau minuman yang telah disuguhkan terdahap diri kita, faktor yang menyebabkan terjadinya adat kemponan yaitu untuk menghindari malapetaka yang akan datang kepada diri kita jika kita sudah kemponan. akibat hukum jika tidak menerapkan adat kemponan akan mendapatkan melapetaka atau kecelakaan bahkan bisa sampai merenggut nyawa. Upaya yang dapat dilakukan untuk terus dapat melestarikan adat kemponan ialah dengan mensosialisasikan secara rinci terhadap masyaraat melayu sambas sebab masih ada masyarakat melayu sambas yang masih berpandangan buruk terhadap adat kemponan. jadi alangkah bagiknya lembaga adat melayu sambas mengadakan sosialisasi kepada masyarakat terkait adat kemponan.Kata Kunci: Adat, Adat Kemponan, Melayu Sambas